Predictive factors for the diagnosis of autoimmune pancreatitis using endoscopic ultrasound-guided tissue acquisition: a retrospective study in Japan - Keisuke Yonamine; Shinsuke Koshita; Yoshihide Kanno; Takahisa Ogawa; Hiroaki Kusunose; Toshitaka Sakai; Kazuaki Miyamoto; Fumisato Kozakai; Haruka Okano; Yuto Matsuoka; Kento Hosokawa; Hidehito Sumiya; et al. (Clinical Endoscopy)
Background/Aims The factors affecting the detection rate of lymphoplasmacytic sclerosing pancreatitis (LPSP) using endoscopic ultrasound-guided tissue acquisition (EUS-TA) in patients with type 1 autoimmune pancreatitis (AIP) have not been thoroughly studied. Therefore, we conducted a retrospective study to identify the predictive factors for histologically detecting level 1 or 2 LPSP using EUS-TA. Methods Fifty patients with AIP were included in this study, and the primary outcome measures were the predictive factors for histologically detecting level 1 or 2 LPSP using EUS-TA. Results Multivariate analysis identified the use of fine needle biopsy (FNB) needles as a significant predictive factor for LPSP detection (odds ratio, 15.1; 95% confidence interval, 1.62–141; p=0.02). The rate of good-quality specimens (specimen adequacy score ≥4) was significantly higher for the FNB needle group than for the fine needle aspiration (FNA) needle group (97% vs. 56%; p<0.01), and the FNB needle group required significantly fewer needle passes than the FNA needle group (median, 2 vs. 3; p<0.01). Conclusions The use of FNB needles was the most important factor for the histological confirmation of LPSP using EUS-TA in patients with type 1 AIP.